Taking the Field : Soldiers, Nature, and Empire on American Frontiers - Kohout, Amy (Book collections on Project MUSE., 2023)
"In the late nineteenth century, at a time when Americans were becoming more removed from nature than ever before, U.S. soldiers were uniquely positioned to understand and construct nature's ongoing significance for their work and for the nation as a whole. American ideas and debates about nature evolved alongside discussions about the meaning of frontiers, about what kind of empire the United States should have, and about what it meant to be modern or to make "progress." Soldiers stationed in the field were at the center of these debates, and military action in the expanding empire brought new environments into play. In Taking the Field Amy Kohout draws on the experiences of U.S. soldiers in both the Indian Wars and the Philippine-American War to explore the interconnected ideas about nature and empire circulating at the time. By tracking the variety of ways American soldiers interacted with the natural world, Kohout argues that soldiers, through their words and their work, shaped Progressive Era ideas about both American and Philippine environments. Studying soldiers on multiple frontiers allows Kohout to inject a transnational perspective into the environmental history of the Progressive Era, and an environmental perspective into the period's transnational history. Kohout shows us how soldiers-through their writing, their labor, and all that they collected-played a critical role in shaping American ideas about both nature and empire, ideas that persist to the present"--